Evaluación hidráulica en el sistema de captación en ACUALCOS E.S.P. ubicado en la localidad de Chapinero (2023)
This degree work teaches the hydraulic evaluation of the collection and pretreatment system of the ACUALCOS E.S.P drinking water treatment plant, located in the town of Chapinero, in the city of Bogotá Cundinamarca. Initially, visits are made to the different intakes that feed the plant, collecting data such as the measurements of the existing structures, the state in which they are located and the capacity they have to capture the flow required to supply the population. also analyzing the collection box of one of these and the sand trap through which the flow passes.